The Relationship Of Work Family Enrichment And Career Development Among Working Mothers’ At Private Sector In East Malaysia - Jessica Jema, David (Universiti Malaysia Sarawak, (UNIMAS), 2021)
The purpose of this study is to identify the relationship between work family enrichment and working mothers’ career development in private sector. The independent variables in this research is Work Family Enrichment which consist of 4 other variables namely, affect, development, capital and efficiency. A private organization was chosen for this present study. The research was conducted using quantitative research methodology through convenience sampling and questionnaires had been used to collect the data in this study. The data obtained from the respondents were analyses by using “Statistical Package for Social Science” (SPSS). Descriptive statistic was used to analyses the respondents demographic background such as gender, age, department and length of service of respondents. Meanwhile, Pearson Correlation analysis had been choose to analyses and identify the relationship between the independent and dependent variable. Based on the findings, it shows that there was a significant relationship between affect, development, capital and efficiency towards career development among working mothers. Recommendation had been made for HR practitioners, organization and future researchers. HR practitioners should enhance should improve on how to manage their own employees especially for the working mothers. Organization suggested to come up with the policy provide a guidance to the employees regarding the Work Family Policy. Last but not least, future researchers are encourage to conduct analysis from public sector and also should proposed to do research based on qualitative study.